ELEPHANT FOOT YAM (AMORPHOPHALLUS CAMPANULATUS ROXB. BLUME) CV. GAJENDRA INTRODUCTION WITH SPICE INTERCROPPING: YIELD EFFICIENCY UNDER SLOPPY FOOT HILLS OF IMPHAL-EAST - RAVI KIRAN THIRUMDASU; A. K. BIJAYA DEVI; MOMOKO THOKCHOM (The Bioscan, 2015)
During the year 2013 from May to November initial study under sloppy foot hills of Imphal-East, Manipur was conducted on acridity free elephant foot yam (Amorphophallus campanulatus Roxb. Blume) cv. Gajendra intercropping with spice crops (ginger and turmeric) for yield efficiency. Elephant foot yam (13.02 t ha-1), turmeric (42.84 t ha-1) and ginger (36.51 t ha-1) were recorded highest yield as sole crops. Among the intercropped treatments maximum land equivalent ratio (1.43) and elephant foot yam equivalent yield (37.91 t ha-1) were recorded in elephant foot yam intercropped with double row of turmeric. The result clearly indicating that non- acridity elephant foot yam cv. Gajendra intercropped with double row of turmeric would be appropriate for providing nutritional security in addition to profitable returns under sloppy foot hills of Imphal-East.